Estudantes tijucanos em cena: história de suas organizações políticas e culturais (Ituiutaba-MG, 1952-1968) - Franco, Isaura Melo (2014)
The history of students in Ituiutaba-MG in the period that comprehends the years of 1952 to 1968, mainly those bound to student associations, it is constituted as research object of this dissertation. Such temporal delimitation comes of the year of creation of the União Estudantil de Ituiutaba student representation entity at the municipal level, which constituted a milestone for the organization of local students, and is limited until 1968, when most of these subjects were disentailing of the entity, gradually losing strength of organization and action in society. In the course of this research highlight important events relating to the actions of the student movement, on the political, cultural, social and educational scenario present in national and regional level in the 1950s and 1960s. Here is also a brief history of the municipality of Ituiutaba and its educational setting until the 1960s as a way to contextualize the horizon on which stood the principal actions of the students in Ituiutaba. This study enabled us to perform reflections about the genesis, performance and weakening of the student movement in this city, and to identify and analyze the actions of a political nature made by this. We observed much of the cultural practices experienced by students represented by unions, clubs and other student bodies of the four local high schools, revealing the common educational principles that circulated in this scenario. Furthermore, it was possible to identify the student profile reported in the press in that context. Therefore, we use as main source of research collections of five newspapers that circulated in Ituiutaba in the 1950s and 1960s. Also resorted to oral history, through semi structured interviews the four student leaders from the investigated context, and analysis of the Minutes of the City Hall of Ituiutaba, photographs of schools and students, works of memoirists and documents of secondary level schools investigated as their internal regulations and inspection reports. So we conducted a cross between discussed sources, compared to the bibliography on the theme, always relating the local context with the national. Overall, this work allows us to understand the history of these important subjects of the educational process has been marked by activities that they conformed to the then prevailing political system, especially from the military dictatorship.